Contact and perspective taking improve humanness standards and perceptions of humanness of older adults and people with dementia: a cross-sectional survey study. (15th June 2017) - Miron, Anca M.; McFadden, Susan H.; Hermus, Nathan J.; Buelow, Jennifer; Nazario, Amanda S.; Seelman, Katarena
ABSTRACT: Background: No empirical work has systematically explored perceptions of humanness of people with dementia and of older adults and the variables that could improve these perceptions. We thus investigated the role of contact and perspective taking in improving perceptions of humanness of these social groups. To do so, we developed a new concept, humanness standards, defined as the amount of evidence of ability impairment needed to conclude that elderly people and those with dementia have lost personhood. Methods: We used a cross-sectional survey design ( n = 619) to assess participants' humanness standards and perceptions of uniquely human characteristics and human nature characteristics of two social groups (people with dementia and older adults). Half the participants ( n = 311) completed a survey about people with dementia and half ( n = 308) assessed older adults. Results: People with dementia were perceived as possessing humanness characteristics to a lesser extent than were older adults. For both groups, contact predicted enhanced perceptions of humanness characteristics. Participants' degree of contact with individuals with dementia also predicted humanness standards, but only under low perspective-taking conditions. As predicted, for older adults, participants set the highest humanness impairment thresholds in the high contact/high perspective-taking condition. Conclusions: We conclude that while social programs that bring persons with dementia and other individuals in contact could change humanness standards and perceptions of humanness characteristics of people with dementia, in the case of elderly adults, the contact must be supplemented by variables that facilitate taking the perspective of the person.